PENGARUH STRUKTUR CORPORATE GOVERNANCE DAN KONTRAK HUTANG TERHADAP PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rei Adrianto; Idrianita Anis (Jurnal Akuntansi Trisakti, 2014)
Earning management is management action that has shape of interference in course offinancial statement compilation with a view to improve its prosperity in personal andalso company value. The thesis is being written to analyzing influence corporategovernance structure and debt covenant toward earnings management onmanufacturing companies listed in Indonesia Stock Exchange. Election Method sampleuses purposive sampling method with population is manufacturing companies thatlisted in Indonesia Stock Exchange. There are 36 samples of manufacturing companies with perception period for three years (2009 till 2011). Data processed using SPSS software for windows.